Ongoing Training Mediated by Technologies in Primary Health Care: Systematic Review - Souza Rockenback, Luana Daniela de; Barbosa, Débora Nice Ferrari; Bez, Marta Rosecler (Journal of Health Care, 2021)
Increasingly, technology combined with teaching has demonstrated significant gains in the development of new learning approaches.  For health professionals, continuing education is an important transforming factor, both in collective spheres and in the community.  In order to identify learning models applied in primary health care aiming at permanent education, the elements/guidelines of a permanent training process of nursing professionals in primary care and considering the use of digital technologies, a systematic literature review was developed. The protocol developed was based on the method of PetersenÂ¹, performing the search in 4 research bases directed to the interest area. Follows, the study was conducted and its results are presented, as well as a critical discussion of the studies analyzed.
Keywords: Teachings models. Technologies. Training. Primary health care